The Promotion and Development of Solar Photovoltaic Industry: Discussion of Its Key Factors - Lin, Grace TR (Distributed Generation & Alternative Energy Journal, 2011)
Due to the severe greenhouse effect and the decreasing reserve of fossil fuels, governments in the world have put more emphasis on the strategic use of renewable energy. Taiwan also considers the solar photovoltaic industry to be one of its important industry targets con- cerning effective and efficient renewable energy exploitation. However, the development of solar photovoltaic industry, in comparison to other high-technology innovation developments in this island country, is still way behind. This research adopts Porter’s diamond model as a theoreti- cal basis and uses the decision-making trial and evaluation laboratory (DEMATEL) to explore how to establish the competitiveness of Taiwan’s solar photovoltaic industry based on the interactions among factors of industrial development. Our empirical results show that demand con- ditions, government support, and related supporting industries are three factors that mainly affect the country competitiveness of its so- lar photovoltaic industry. Factor conditions and firm strategy, structure, and rivalry are then the affected factors of the establishing of Taiwan’s competence in solar photovoltaic industry. Moreover, according to prag- matic results, this research provides policy suggestions for the related authorities to refer.